Cell individuality in adhesin expression of Candida glabrata - Halliwell, Samantha Clare (2012)
Clonal cell populations are known to exhibit marked phenotypic heterogeneity at the single cell level, a phenomenon usually masked by conventional population-wide analyses. Two models of yeast cell heterogeneity were investigated during this study. First, expression of the Saccharomyces cerevisiae Rad6 protein, known to facilitate DNA damage tolerance, was investigated. However, apparent bimodal Rad6 expression proved to be an artefact of a mixed-genotype culture source. The other model was adhesin expression heterogeneity in the opportunistic yeast pathogen Candida glabrata. Adherence to the host cell is an important step in the establishment of C. glabrata infection, mediated by adhesin proteins. The subtelomeric EPA family of adhesin genes encodes a large class of GPI-anchored cell wall proteins in C. glabrata, among which Epa1 is the best studied. Epa1 expression is highly heterogeneous between individual C. glabrata cells, a factor that can dictate adherence capacity and may have important implications for infection. Such cell-to-cell variability was dependent upon strain background. Variation in cell surface Epa1 level was correlated with variation in EPA1 mRNA, consistent with transcriptional regulation of heterogeneity. Indeed Sir-dependent silencing was found to be a major driver of heterogeneous Epa1 expression in a strain demonstrating high cell-to-cell variability but not in an alternative genetic background demonstrating lower heterogeneity. Inefficient silencing in the latter strain was overcome by ectopic SIR3 expression, and was not due to differences in EPA1 sequence or distance from the chromosome end compared with the heterogeneous strain. Moreover, strain-to-strain variation in the silencing-dependence of EPA1 expression was observed across a range of clinical isolates and was found to correlate with the extent of Epa1 heterogeneity. Thus, marked variation in adhesin expression exists between cells and between strains of C. glabrata. In addition, the data presented shed light on the regulation of such heterogeneity in particular the role of Sir-dependent transcriptional silencing.